THE IMPACT OF DUST POLLUTION FROM UNPAVED ROADS IN THE AKAMAS PENINSULA, CYPRUS, USING UAV AND SENTINEL-2 IMAGES - Themistocleous, Kyriacos; Prodromou, Maria (My University, 2023)
This study examines the effects of dust in the Akamas National Park in Cyprus generated from traffic over the unpaved roads on the roadside vegetation. The Akamas National Park is located on the western tip of Cyprus and covers an area of about 230 km², containing valleys, gorges and wide sandy bays. Akamas is a mountainous, relatively inaccessible area to standard vehicles and protected from man-made development. It is home to hundreds of animal species and plants that are essential for the ecology of the Mediterranean region. There are several unpaved roads to access the area and more than one million people visit the Akamas peninsula each year, mostly in the summer period, primarily in 4X4 and all-terrain vehicles, which are rented in the nearby area. This unregulated traffic results in dust, especially during the dry weather conditions in the summer that can fall up to a kilometre away on all sides of the vehicle. In this study, images acquired from an Unmanned Aerial Vehicle (UAV) of the roads within the Akamas peninsula were compared with Sentinel-2 satellite images during different seasons. Using the Normalized Vegetation Index (NDVI) from the Sentinel-2 images, it was shown that the vegetation nearest to the unpaved roads exhibited pronounced stress compared to the vegetation that was more distant. Also, spectral signatures as well as infrared and thermal images were taken at different distance intervals from the unpaved road.
Keywords: Akamas; NDVI; Dust pollution; Sentinel-2; spectral signatures; thermal and infrared images